PENERAPAN KAIDAH FIKIH AL-ADAH MUHAKKAMAH DALAM PEMBAGIAN HARTA WARISAN PADA MASYARAKAT ISLAM DI KECAMATAN TANETE RIATTANG KABUPATEN BONE - Fitrah Nisardi; Supardin Supardin; Andi Muhammad Akmal (Qadauna: Jurnal Ilmiah Mahasiswa Hukum Keluarga Islam, 2023)
The discussion in this study is related to the application of the fiqh rules of al-adah muhakkamah in the distribution of inheritance to the Islamic community in Tanete Riattang District, Bone Regency. Fundamentally related to inheritance matters have been regulated in Islamic law, but in reality not all Muslims share the inheritance with reference to the provisions regarding the distribution of inheritance in the fiqh Mawaris. Customs and habits that grow in a person's social environment, become the reason that person is bound by a law. There are at least two concepts of inheritance law in Indonesia, namely, Islamic law and customary law. In this study, several main issues were formulated, including the form of inheritance distribution as well as the implementation of the application of the principles of fiqh al adah muhakkamah. by tudang sipulung or by deliberation. The concept of sharing inheritance is in accordance with the concept of tashaluh sharing which is based on agreement and voluntarism. The implementation of the distribution of inheritance by tudang sipulung is in accordance with the distribution according to Islamic law, in this case al-adah or al-urf, as long as the distribution of inheritance does not conflict with the values of Islamic teachings. The division using this method is based on the agreement and also the voluntarism of the heirs, which is basically the same as the distribution of inheritance by means of tashaluh which in practice prioritizes deliberation and agreement of the heirs. Keywords: Customary Law, Inheritance, Fiqh Rules.